PERAN PEMERINTAH DALAM MENGANTISIPASI TERJADINYAPERSAINGAN USAHA TIDAK JUJUR BERDASARKANUNDANG-UNDANGNOMOR20TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Muhammad Ferdian (Fakultas Hukum Universitas Kristen Indonesia, 2017)
Abstract Business competition is often found whose business competition is dishonest, especially towards trademarks. In terms of minimizing the occurrence of violations of unfair business competition, the government has a very im- portant role. The government needs to conduct socialization related to fair business competition on trademarks, by: conducting education, campaigns, providing understanding, providing training for of cers in the Directorate General of Intellectual Property, inviting the public in the ght against counterfeiting and imitation, and the exis- tence of monitoring, evaluation , and fostering by the Directorate General of Intellectual Property or the Business Competition Supervisory Commission (KPPU) and conducting strict reprimands and legal sanctions for business actors who continue to violate their business activities and are proven, then Law Number 20 Year 2016 concern- ing Trademarks and Geographical Indications , speci cally regulates the provision of criminal sanctions that are included in the provisions of Articles 100 and 102. Keywords: business competition; dishonest; KPPU; legal sanctions.